Counselling experiences among men having sex with men and living with HIV in Malaysia - Tuan Norbalkish Tuan Abdullah; Ruhani Mat Min; Siti Salina Abdullah; Mosharaf Hossain (PLoS ONE, 2022)
Purpose In Malaysia, the trend of HIV transmission has shifted from intravenous drug use to sexual intercourse, and men who have sex with men (MSM) have become the main driver due to high-risk sexual behaviour. Thus, treatment and care, which also involves counselling, for men who have sex with men and who are living with HIV (MSM living with HIV) are crucial. This study aims to explore the experiences of MSM living with HIV and participating in counselling session during treatment and care at two public hospitals. Method This qualitative study with a grounded-theory approach was conducted at two public hospitals in Malaysia. Five participants who were MSM living with HIV were selected through purposive sampling. They participated in semi-structured interviews, non-participant observations, and diary entries, each of which was conducted three times. The data were analysed using grounded theory with N-Vivo 8 to determine themes. Result The participants were found to experience feelings of emptiness and hopelessness because of their unreadiness to accept their HIV status. These feelings made their participation in counselling sessions challenging. Consequently, the participants found counselling sessions unhelpful due to their unwillingness to participate in the counselling relationship. Conclusion The findings of the study highlight the need for counselling sessions to focus more on feelings related to unreadiness to improve the self-esteem and ability to create positive relationships with others of MSM living with HIV. It is also important to strengthen the training and skills among HIV counsellors to enhance counselling services for these men.